Leishmaniasis: Who Uses Personal Protection among Military Personnel in Colombia? - Aida M. González; María Teresa Solís-Soto; Katja Radon (Ubiquity Press, 2017)
Background: Leishmaniasis is common in Colombia, negatively affecting the health of military personnel active in endemic areas. The disease is transmitted by sand fly bites. Therefore, during duty, use of long-sleeved uniforms and other clothes treated with permethrin and application of mosquito repellent are important personal preventive measures. Objective: The objective of this study was to assess personal and occupational factors associated with the use of personal protection in male soldiers deployed to Leishmaniasis-endemic areas. Methods: Three hundred soldiers participated in a cross-sectional questionnaire study (response 84.3%). The self-administered questionnaire contained questions about sociodemographics, duration of service, compliance with personal mosquito protection, and knowledge about leishmaniasis. Descriptive analyses were followed by multiple logistic regression models adjusted for potential confounders (EpiInfo Version 7.0. Findings: Overall, 23% of the soldiers reported complete use of the recommended personal protection measures. About 83% of the participants had heard about leishmaniasis. In the adjusted regression model, knowledge about leishmaniasis (adjusted odds ratio = 2.9; 95% confidence interval: 1.1-7.2) and being enrolled in the army for more than 5 years (2.2; 1.1-4.1) increased the odds of using personal protection. Conclusions Improving knowledge about leishmaniasis is one measure to increase use of personal protection, thereby diminishing the risk of infection.